EVALUASI DAYA TAMPUNG BEBAN PENCEMARAN PERAIRAN DAS BATURUSA DENGAN MODEL QUAL2KW - Pratiwi, Fika Dewi; Gustomi, Andi; Setiawan, Fahri; Manalu, Yeni Saro; Nugraha, Mohammad Agung (Jurnal Penelitian Perikanan Indonesia, 2023)
Pollutants originating from various human activities (households, pepper and oil palm plantations, Vanname shrimp farming, ship docks, tin mining) in the Baturusa watershed area make the watershed critical. Based on these problems, it is urgent to determine the carrying capacity of pollution loads in order to be able to analyze the capacity of the watershed to receive input pollutant loads. Therefore, this study aims to analyze the pollution load of the Baturusa watershed and analyze the carrying capacity of the pollution load using Qual2Kw numerical modeling. This field research was carried out in June-July 2023 using a survey method. The location was selected purposively at eleven sampling points in the form of main rivers and tributaries in the Baturusa watershed area. Sampling used the grab sampling method. Based on the Qual2Kw model, the nitrate and COD can be modeled well with the RMSE indicator value <1. The opposite was obtained for TSS and total nitrogen parameters, with RMSE values >1. The pollution load for the parameters of nitrate, total nitrogen and TSS, COD received by the main river of the Baturusa DAS has not exceeded the maximum pollution load for class II, so it still has the capacity to accommodate activities around the study site. Based on these conditions, integrated management from upstream to downstream is required for the preservation of the Baturusa watershed and sustainable use.